The Meaning of Menstruation in Women with Mild Disabilities - Rahmah, Siti; Wike; Ratnawati, Retty (The Center for Disability Studies and Services Brawijaya University, 2022)
Women with Disabilities have a greater social vulnerability both as Women and Persons with Disabilities. The stigma formed by the community greatly influences them in interpreting their menstruation. This study aims to explore the meaning of menstruation for women with mild disabilities. This research was conducted qualitatively using Alfred Schutz's Phenomenological Approach and supported by Symbolic Interactionism Theory and Radical Feminist Theory. The results of the study found the concept of menstruation, the concept of personal hygiene during menstruation, and gender relations in menstruation. The implications of this research are 1) Implementation of health policies related to reproductive health services for women with disabilities; 2) Menstruation socialization and counseling for Women with Disabilities and their families; 3) Capacity building of Social Welfare Institutions related to Gender and Reproductive Health; 4) Development of skills training for making cloth pads for women with disabilities and their families.